Mix Metal Thermal Stabilizer from Palm Fatty Acid Distillate - Octavia, Yona; Putrawan, I Dewa Gede Arsa (Eksergi, 2025)
Polyvinyl chloride (PVC) is a widely utilized material across various fields; however, it is prone to thermal degradation, even at temperatures as low as 70°C. To enhance its thermal stability, the addition of thermal stabilizers is essential. Mixed metal stabilizers are among the most environmentally friendly and effective options, composed of carboxylate acids and a combination of alkaline earth and transition metals. This study aims to synthesize a Ca/Zn-based mixed metal stabilizer using Palm Fatty Acid Distillate (PFAD), a locally available raw material with significant potential as a source of carboxylate acid. The synthesized stabilizer, termed "Ca/Zn palmat," utilizes calcium (Ca) and zinc (Zn), chosen for their non-toxic properties. FTIR analysis confirmed the successful formation of Ca/Zn carboxylate groups from PFAD. The optimal Ca:Zn ratio was determined to be 4:1, providing a PVC stability time of approximately 15 minutes based on the Congo red test. The ideal stabilizer dosage was found to be 7 phr (parts per hundred resin). Furthermore, the addition of pentaerythritol as a co-stabilizer demonstrated a synergistic effect, significantly enhancing the thermal stability of PVC